2014
DOI: 10.3892/mmr.2014.1946
|View full text |Cite
|
Sign up to set email alerts
|

Propofol selectively inhibits nuclear factor-κB activity by suppressing p38 mitogen-activated protein kinase signaling in human EA.hy926 endothelial cells during intermittent hypoxia/reoxygenation

Abstract: Abstract. Intermittent hypoxia/reoxygenation (IHR) induces proinflammatory cytokines, contributing to the pathogenic process of atherosclerosis associated with obstructive sleep apnea (OSA). Two transcription factors, nuclear factor-κB (NF-κB) and hypoxia-inducible factor-1 (HIF-1), have been indicated to mediate proinflammatory cytokines during IHR. The anti-inflammatory effects of propofol have attracted increasing attention in regard to the treament of multiple diseases associated with inflammation. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
2
14
1
Order By: Relevance
“…A recent report clarified that triroside attenuated the neuroinflammation in microglia via NF-κB and p38 MAPK signalling pathways [28]. Furthermore, propofol suppressed the NF-κB-mediated inflammation by prohibiting the activation of p38 MAPK in IH-treated vascular endothelium [16]. Consistently with previous reports, IH-induced activation of NF-κB and p38 MAPK both were dramatically reduced by propofol treatment in the present study.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…A recent report clarified that triroside attenuated the neuroinflammation in microglia via NF-κB and p38 MAPK signalling pathways [28]. Furthermore, propofol suppressed the NF-κB-mediated inflammation by prohibiting the activation of p38 MAPK in IH-treated vascular endothelium [16]. Consistently with previous reports, IH-induced activation of NF-κB and p38 MAPK both were dramatically reduced by propofol treatment in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…A wealth of information linking that propofol prohibited inflammatory response through preventing the NF-κB and p38 MAPK signalling and then reducing the release of inflammatory mediators is published [25,26]. In addition, emerging evidence showed that propofol selectively attenuated the activation of NF-κB and p38 MAPK in vascular endothelium during IH exposure [16]. The effect of propofol on IH treated microglia was still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PI3K/Akt and p38 MAPK pathway exists extensively in cells and is involved in the regulation of a series of physiological activities such as cell apoptosis. Both propofol and sevoflurane were reported to regulate AKT and p38 expression levels [47][48][49]; however, this phenomenon was not observed in our study. As expected, propofol increased the phosphorylation of AKT but decreased the phosphorylation of Bad, while no changes were detected in the expression or phosphorylation of p38.…”
Section: Discussioncontrasting
confidence: 56%
“…In addition, propofol demonstrates anti-inflammatory properties by decreasing the production of proinflammatory cytokines, including tumor necrosis factor-alpha and interleukins 1, 6, 8, and 10; inhibits neutrophil chemotaxis, cellular attachment and migration, phagocytosis, production of inducible nitric oxide synthase, and reactive oxygen species; scavenges free radicals; decreases lipid peroxidation; and inhibits platelet aggregation [26,29]. Li et al [30] reported that propofol may have the potential to prevent atherosclerosis in patients by inhibiting nuclear factor-κB (NF-κB)-mediated inflammation in the vascular endothelium. In addition, Hsing et al [31] demonstrated that propofol decreased NF-κB, but increased PPARγ, expression in lipopolysaccharide stimulated rat mesangial cells.…”
Section: Introductionmentioning
confidence: 98%